2005
DOI: 10.1097/01.mpg.0000177314.65824.4d
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Prevalence of Nonalcoholic Fatty Liver Disease in Black Obese Children

Abstract: Eight percent of asymptomatic, obese children had an elevated ALT suggestive of NAFLD. White and very obese children are more likely to be affected. Sex and age are not good clinical predictors of NAFLD. We suggest that all obese children be screened for NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 24 publications
(37 reference statements)
6
46
1
2
Order By: Relevance
“…Previous research has shown a decreased prevalence of NAFLD in black obese children. [33] Presence of the MS was associated with an increase in fatty liver on US, as well as in increase in ALT and GGT. The majority of the NAFLD literature reports elevated ALT as more highly associated with NAFLD than GGT.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown a decreased prevalence of NAFLD in black obese children. [33] Presence of the MS was associated with an increase in fatty liver on US, as well as in increase in ALT and GGT. The majority of the NAFLD literature reports elevated ALT as more highly associated with NAFLD than GGT.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to gender differences, rates of NAFLD differ among ethnic groups. The lowest rates of NAFLD were found among African Americans [14][15][16][17][18][19]. Particularly disturbing was the high rate of NAFLD observed in Hispanic youths [17].…”
Section: Introductionmentioning
confidence: 88%
“…African Americans have also been shown to have larger LDL particles in comparison to their Caucasian peers (29). Similarly, African Americans have a lower prevalence of NAFLD in comparison to Caucasians (30). In contrast to their seemingly favorable lipid profile, AfricanAmerican children and adolescents have a greater systolic blood pressure per given degree of obesity and display differences in renal handling of potassium (31).…”
Section: Impact Of Genetic Intrauterine Andmentioning
confidence: 99%